Die Kosten der Flüchtlingskrise in Deutschland – eine Investition in die Zukunft? - Volker Brühl (Wirtschaftsdienst, 2016)
In einem finanzökonomischen Modell zeigt sich, dass der "fiskalische Break-even-Point" 2031 möglich ist. Dann könnten erstmalig die Steuern und Abgaben der erwerbstätigen die Kosten der nicht erwerbstätigen Flüchtlinge übersteigen. Der "ökonomische Break-even-Point" kann bereits 2025 erreicht werden, wenn die Bruttowertschöpfungsbeiträge der dann erwerbstätigen Flüchtlinge die Kosten der Versorgung und Integration der nicht erwerbstätigen Flüchtlinge übersteigen. Voraussetzung sind hohe Investitionen in die individuelle Qualifizierung und eine flexible Anwendung arbeitsmarktpolitischer Instrumente. – – The high costs of the refugee crisis are often a subject of public discussion. However, one should distinguish between the fiscal and the overall economic effects of this current wave of immigration. A financial economic model shows that the "fiscal break-even" point can be reached by the year 2031. This is the first point at which the taxes and contributions of employed refugees exceed the costs to the public sector resulting from the refugees who are not in the labour market. The "economic break-even" point can be reached as early as 2025 if the gross value added contributions of the employed refugees by that time exceed the costs of caring for and integrating the refugees who are not in employment. This will require a "smart" integration of the refugees into the labour market, requiring high investment in the qualification of individuals and a flexible use of labour policy tools.
Keywords: F20; F22; F60; 330; Flüchtlinge; Soziale Kosten; Soziale Integration; Beschäftigungseffekt; Simulation; Deutschland